Enriched Environments as a Potential Treatment for Developmental Disorders: A Critical Assessment - Ball, Natalie J.; Mercado, Eduardo; Orduña, Itzel (Frontiers in Psychology, 2019)
The beneficial effects of enriched environments have been established through a long history of research. Enrichment of the living conditions of captive animals in the form of larger cages, sensory stimulating objects, and opportunities for social interaction and physical exercise, has been shown to reduce emotional reactivity, ameliorate abnormal behaviors, and enhance cognitive functioning. Recently, environmental enrichment research has been extended to humans, in part due to growing interest in its potential therapeutic benefits for children with neurodevelopmental disorder (NDDs). This paper reviews the history of enriched environment research and the use of enriched environments as a developmental intervention in studies of both NDD animal models and children. We argue that while environmental enrichment may sometimes benefit children with NDDs, several methodological factors need to be more closely considered before the efficacy of this approach can be adequately evaluated, including: (i) operationally defining and standardizing enriched environment treatments across studies; (ii) use of control groups and better control over potentially confounding variables; and (iii) a comprehensive theoretical framework capable of predicting when and how environmental enrichment will alter the trajectory of NDDs.